2020
DOI: 10.1192/bjo.2020.68
|View full text |Cite|
|
Sign up to set email alerts
|

Subjective cognitive functioning in relation to changes in levels of depression and anxiety in youth over 3 months of treatment

Abstract: Background Subjective cognitive difficulties are common in mental illness and have a negative impact on role functioning. Little is understood about subjective cognition and the longitudinal relationship with depression and anxiety symptoms in young people. Aims To examine the relationship between changes in levels of depression and anxiety and changes in subjective cognitive functioning over 3 months in help-seeking youth. Method This was a cohort study of 656 youth ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Subjective cognitive functioning was assessed at three‐month follow‐up using the NSSR (Allott et al., 2020; Fisher et al., 2016). The NSSR is an eight‐item self‐report questionnaire that assesses an individual’s subjective changes in cognitive functioning (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjective cognitive functioning was assessed at three‐month follow‐up using the NSSR (Allott et al., 2020; Fisher et al., 2016). The NSSR is an eight‐item self‐report questionnaire that assesses an individual’s subjective changes in cognitive functioning (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Participants with mild to moderate depression more often perceived their cognitive function to have improved since commencing treatment, compared to those with moderately severe to severe depression (Fisher et al., 2016). More recently, the NSSR was administered to a larger independent cohort of young people aged 12–25 ( N = 656) after they had been enrolled in treatment at a primary care mental health setting (Allott et al., 2020). Approximately a quarter to one‐third of the sample reported subjective improvement in their cognitive functioning after three months of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less research about subjective cognitive function has been conducted in youth depression samples, whose experience of cognitive problems associated with depression may be different if depression onset is relatively recent. In their analysis of depression symptoms over 3 months, and perceived change in subjective cognitive function, Allott et al 13 (this series) reported that improvement or reduction in self-rated depression symptoms was highly associated with change in subjective ratings of cognitive function in their youth sample. That is, patients who reported improvement in their mood also felt their cognitive functions had strengthened.…”
Section: Subjective Versus Objective Impairment Of Cognitive Functionmentioning
confidence: 99%
“…Similarly, people who primarily suffer from these psychiatric disorders often report sub-optimal cognitive performance, further emphasising the intertwined relationship between affective burden and subjective cognitive experience (Millan et al, 2012). Moreover, treating anxiety and depression may improve subjective cognitive complaints in individuals with SCI (Allott et al, 2020). Despite the association between SCI and affective burden being increasingly recognised, little is understood about the underlying cognitive mechanisms and brain networks involved.…”
Section: Introductionmentioning
confidence: 99%